HIDDEN IN PLAIN SIGHT: MULTIFOCAL PARAGANGLIOMA IN AN ADOLESCENT WITH HYPERTENSION - Kannan, Muvennthen; Shukor, Ahmad Zulkifli Bin Mohamed; Naidu, Thaalitha; Ahmad, Nur Shida Binti (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors. The high incidence of multifocality, recurrence and metastatic disease complicates the management of paraganglioma in adolescents. CASE A previously healthy 14-year-old male presented with a one-month history of occipital headache associated with blurring of vision. He had no chest pain, dyspnoea, diaphoresis or syncope. There is no family history of hypertension in the young. His mother has hyperthyroidism. On arrival, his blood pressure was 242/167 mm Hg, heart rate was 127 bpm, and SpO₂ was 100% on room air. His capillary blood glucose was normal at 4.8 mmol/L. Physical examination showed no signs of goitre, cushingoid features, or acromegalic traits. The patient is overweight, with a BMI of 25.6 kg/m². He showed no stigmata of neurofibromatosis. Fundoscopy showed bilateral optic disc swelling and macular edema, consistent with grade IV hypertensive retinopathy. Electrocardiogram revealed sinus tachycardia with T-wave inversion in lead V2–V6. Laboratory investigations, including complete blood count, calcium and renal profile, were unremarkable. His endocrine workup confirmed a diagnosis of pheochromocytoma with elevated 24-hour urinary normetanephrine (90.75 µmol/day, 36.5× ULN) and 3-methoxytyramine (4.02 µmol/day, 2.8× ULN). Adrenal CT imaging revealed a large, lobulated, heterogeneously enhancing mass measuring 5.0 × 6.1 × 5.4 cm (AP × W × CC) along the left margin of the abdominal aorta. The bilateral adrenal glands are normal. Neck and Thorax CT showed a well-defined, round, homogeneously enhancing lesion at the base of the skull measuring 1.0 × 1.1 × 1.4 cm (AP × W × CC). Therefore, he was diagnosed with paraganglioma. His blood pressure is currently controlled with three antihypertensive medications, including an alpha blocker. Given his multifocal disease, germline genetic testing is warranted, and functional imaging should be considered preoperatively to exclude metastasis. He was referred to an endocrine center for further management. CONCLUSION Pediatric PPGLs are more often extra-adrenal, multifocal/metastatic, and recurrent, likely due to a stronger genetic predisposition. Hence, timely diagnosis is crucial to prevent morbidity and mortality.